2023
DOI: 10.1001/jamanetworkopen.2023.9602
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Care and Emergency Department Use During the COVID-19 Pandemic Among Patients of Family Physicians in Ontario, Canada

Abstract: ImportanceThe COVID-19 pandemic has played a role in increased use of virtual care in primary care. However, few studies have examined the association between virtual primary care visits and other health care use.ObjectiveTo evaluate the association between the percentage of virtual visits in primary care and the rate of emergency department (ED) visits.Design, Setting, and ParticipantsThis cross-sectional study used routinely collected administrative data and was conducted in Ontario, Canada. The sample compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We also build on a previous Ontario-based study in which we found that patients who had visits with virtual walk-in clinics in 2020 were twice as likely as those with other types of virtual family physician visits to visit the emergency department within 30 days. In addition to better addressing potential sources of confounding, this study extends our findings to 2021, when emergency department visit volumes began to rise to their pre-COVID-19 levels …”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also build on a previous Ontario-based study in which we found that patients who had visits with virtual walk-in clinics in 2020 were twice as likely as those with other types of virtual family physician visits to visit the emergency department within 30 days. In addition to better addressing potential sources of confounding, this study extends our findings to 2021, when emergency department visit volumes began to rise to their pre-COVID-19 levels …”
Section: Discussionmentioning
confidence: 56%
“…Within-system virtual care (integrated with in-person, office-based care) from US-based Intermountain Healthcare and Kaiser Permanente has compared more favorably with in-person care than has direct-to-consumer telemedicine, which has been associated with increased downstream health care use and costs . In 2 Ontario studies, patients whose regular family physicians provided more virtual care did not have higher rates of emergency department use. Furthermore, within-system virtual care has demonstrated the potential for associated increases in equity of care via improved access for individuals who struggle to afford higher visit-related costs …”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, virtual care and virtual end-of-life care use in Ontario rapidly increased [ 4 , 5 ]. Emerging evidence suggests that the use of virtual care for people attending a walk-in clinic during the pandemic was associated with higher use of the emergency department, which may depend upon the type of care received and the provider delivering it [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual care use increased during the COVID-19 pandemic, especially during pandemic lockdowns [ 16 , 17 ], and evidence is emerging that virtual care may be effective in strengthening access to primary care in rural and remote communities [ 18 ]. Findings show that more virtual care from family physicians during the COVID-19 pandemic did not result in more ED use [ 19 ]. However, especially in the context of the COVID-19 pandemic, there are many services that can only be delivered in person, such as COVID-19 nasal swab testing.…”
Section: Introductionmentioning
confidence: 99%